Irrigation economics in poor countries : illustrated by the Usangu Plains of Tanzania - Hazlewood, Arthur; Livingstone, Ian. (Oxford ; New York : Pergamon Press, 1982)
This book examines issues in irrigation from the viewpoint of the economist. Topics covered include: The calculation of irrigation potential; The demand for water; The supply of water; The economics of water storage; Analysing the economic structure of a river basin; Assessing production potential and social structure; The economics of smallholder irrigation; irrigation and integrated rural development and economics and technology.
Includes index.
lje 11/5/17
Loans.
Keywords: Avid regions; Underdeveloped areas---Irrigation; Irrigation---Economic aspects; Developing countries